Cutaneous signet-ring cell squamous cell carcinoma. Issue 3 (2nd July 2020) - Findeis, Sarah K.; Readinger, Allison; Mitchell, James; Agarwal, Atin
Abstract: Cutaneous signet-ring cell squamous cell carcinoma (SRCSCC) is a rare variant, most commonly occurring in the head and neck. We report a case of a 66-year-old transgender woman with an ulcerated growing facial mass measuring 5.6 × 4.0 × 2.0 cm. Histological analysis showed features consistent with SRCSCC. Immunohistochemical analysis showed positive staining for high-molecular-weight cytokeratin, estrogen receptor (1-2+ in 10%), E-cadherin (mostly positive with partial loss), and p40 and negative staining for Ber EP-4, cytokeratin 7, low-molecular-weight cytokeratin, mucicarmine, Alcian blue PAS, HER2, and MUC4. The tumor had invaded the perineurium, lymphovascular spaces, and subcutaneum. Additionally, microsatellite instability testing was negative. This case adds to the limited knowledge of this poorly characterized entity.